Community Media and Communitarianization of Dakwah Radio Rodja 756 Am - Lubis, Canra; Rosidi, Rosidi (KOMUNIKA, 2022)
This research wants to prove that communication with community radio media has an important place to gain space in the hearts of the community in an effort to broadcast Islamic da'wah. It turns out that according to the theory used in this study, the application of bottom-up da'wah is able to practice sunnah Islamic values in the family environment, the community around the Rodja radio location. The presence of this radio is able to foster religious awareness, become a source of knowledge for mankind in general and especially for Muslims.If media such as radio and television are used to advocate and educate people in the way of Allah SWT, it will benefit people wherever they are, but for non-Muslims, a complete understanding of Islam.This research is a type of field research, using qualitative methods, with a philosophical and historical approach. The main source of this message is data related to its role and radio Rodja's religious activities. Besides that, it is also supported by previous research data which is complemented by books, magazines, and related documents. This data was collected through interviews, documents, notes, and social, psychological and communication uses.